Assessment of Fluid Responsiveness With End Tidal Carbon Dioxide Using A Simplified LegRaising Maneuver in Non-Cardiac Patients Admitted in Medical Intensive Care Unit - Hassan, Zubia; Fazal, Imran; Ashraf, Nadeem; Hayat, Arshad; Sajjad, Kaswar; Zaman, Asad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the fluid responsiveness with end tidal carbon dioxide using a simplified leg-raising maneuver in noncardiac patients admitted in medical Intensive Care Unit (ICU).Study Design: Cross sectional analytical study.Place and Duration of Study: Intensive Care Unit, Pak Emirates Military Hospital Rawalpindi, form Jun to Nov 2019.Methodology: A total of 80 cases were included in this study who were admitted in medical ICU and were on ventilator support. A standard 5-minute leg-raising maneuver was applied on all the patients. An increase in cardiac index >15% after passive leg rise was taken as criteria for responders. All echocardiographic evaluations were performed by experienced sonographers.Results: Mean age of study participants was 47.4 ± 4.421 years, 65 (81.3%) were males while 15 (18.7%) were female patients. Sixty (75%) patients responded to the simplified leg raising maneuver while 20 (25%) did not respond. Mean arterial pressure of the respondents was 92.3 ± 3.26 mmHg while mean arterial pressure of the non-respondents was 83.2 ± 4.57 mmHg. High body mass index and low mean arterial pressure had statistically significant relationship with no response to the maneuver in our study.Conclusion: Simplified leg raising emerged as an effective maneuver to stabilize the non-cardiac patients hemodynamically inside the setting of critical care unit. Patients with low baseline mean arterial pressure or high body mass index may be considered as high risk for non-response to this maneuver.